Meningkatkan Hasil Belajar Siswa SMK Melalui Model Project Based Learning Dengan Media Cisco Packet Tracer - Afandi Husin Amin Syahrul Lubis; Syaiful Bahri; Harry Pratama Figna; Ryan Dhika Priyatna; Ade Evi Fatimah (PT. INOVASI TEKNOLOGI KOMPUTER, 2023)
The application of lecture method as a teaching approach has been proven to be one of the factors contributing to low student grades. This is because the lecture method still revolves around the teacher as the primary source of information without actively involving the students. To address this issue, the solution is to implement Project Based Learning as a teaching method. This research utilized a quasi-experimental design. The population of this study consisted of X TKJ class students. Samples were selected using purposive sampling technique, with X TKJ 1 as the experimental group and X TKJ 2 as the control group. Data collection was conducted through tests and observations. Data analysis was performed using t-test and standardized gain test. Based on the research findings, there was a significant improvement in learning outcomes in the experimental group, with an increase of 78.74 categorized as high. Meanwhile, the control group showed a lower improvement in learning outcomes, with an increase of 28.33 categorized as low. Therefore, it can be concluded that students in X TKJ class, who were taught Jaringan Dasar subject using the Project Based Learning method with Cisco Packet Tracer as the media, exhibited higher improvement in learning outcomes compared to students taught with the lecture method.